Analisis Pengaruh Ketidakamanan Kerja Terhadap Kinerja Karyawan Dengan Komitmen Organisasional Sebagai Variabel Moderating (Studi Pada Karyawan Kontrak Bagian Produksi PT. Inti Sukses Garmindo Semarang) - Anton Christian Hutagaol; Intan Ratnawati (Optimum: Jurnal Ekonomi dan Pembangunan, 2012)
The research was cunducted at PT. Inti Success Garmindo. The number of respondents researched many as 121 employees. i used proportionare sampling or by proportion sampling technique. Collecting data using a quistionare study. Techniques of data analysis in this study are SEM (Structural Equation Model) Based on the results computed by Amos 16 version found the result that the entire hypothesis can be accepted. Job insecurity negatively affect organizational commitment on to the coefficients (H1), the positive effect of organizational commitment on employee performance (H2) and job insecurity negativley affect employee performance (H3). This Study has show that organizational commitment in the first biggest factor affecting the performance of the employee while the second factor is job insecurity. Furthemore the indirect effect of mediation between insecurity on employee performance through the mediation of organizational commitment which means the position of organizational commitment as a mediating variable between job insecurity and employee performance has more influence. based on the above the model purpose in this study can be accepted.